Daniel Carter Beard papers - Beard, Daniel Carter, 1850-1941.; Beard, Daniel Carter, 1850-1941.; Beard, Frank, 1842-1905.; Beard, James Henry, 1812-1893.
Correspondence, diaries, speeches, articles, research material, family papers, printed matter, sketch books, illustrations, photographs, and other papers relating to Beard's career as an author and illustrator and to his leading role in the Boy Scouts of America. Documents his activities with the Culver Military Academy, Culver, Ind.; the Dan Beard Outdoor School, Pike County, Pa.; and the Sons of Daniel Boone. Includes a manuscript of Beard's autobiography, Hardly a Man Is Now Alive: the Autobiography of Dan Beard (1939), articles devoted to outdoor life, and other writings. Also includes correspondence with Samuel Langhorne Clemens pertaining to Beard's illustrations for the first illustrated editions of Connecticut Yankee in King Arthur's Court (1889) and Tom Sawyer Abroad (1894). Family papers include correspondence, writings, and illustrations by members of the Beard family, in particular Beard's father, James Henry Beard, and his brother, Frank Beard.
Correspondents include Robert Stephenson Smyth Baden-Powell, Baron Baden-Powell of Gilwell; Gutzon Borglum; Belmore Browne; Howard Chandler Christy; Samuel Langhorne Clemens; George J. Fisher; Hamlin Garland; Charles Dana Gibson; Zane Grey; Walter W. Head; William Dean Howells; Edwin Markham; Edward Sandford Martin; H.L. Mencken; Albert Bigelow Paine; Maxwell E. Perkins; Gifford Pinchot; Henry C. Pitz; Augustus Post; George D. Pratt; Frank Presbrey; Frederic Remington; Norman Rockwell; Franklin D. Roosevelt; Ernest Thompson Seton; Upton Sinclair; Frederic Dorr Steele; A.J. Stone; Isaac Sutton; Lorado Taft; Hendrik Willem Van Loon; Frederick K. Vreeland; John Quincy Adams Ward; James E. West, Owen Wister; S.J. Woolf; N.C. Wyeth; Boy's Life magazine; and the publishing firms, Charles Scribner's Sons and J.B. Lippincott Company. Also includes correspondence with Theodore Roosevelt; his wife, Edith Kermit Carow Roosevelt; their son, Theodore Roosevelt (1887-1944); and other Roosevelt family members.
Library of Congress Prints and Photographs Division.
Artist, author, editor, and cofounder of the Boy Scouts of America.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baden-Powell of Gilwell, Robert Stephenson Smyth Baden-Powell, -- Baron, -- 1857-1941 -- Correspondence; Borglum, Gutzon, -- 1867-1941 -- Correspondence; Browne, Belmore, -- 1880-1954 -- Correspondence; Christy, Howard Chandler, -- 1873-1952 -- Correspondence; Clemens, Samuel Langhorne, -- 1835-1910 -- Correspondence; Fisher, George J., -- -1960 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Gibson, Charles Dana, -- 1867-1944 -- Correspondence; Grey, Zane, -- 1872-1939 -- Correspondence; Head, Walter W. -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Markham, Edwin, -- 1852-1940 -- Correspondence; Martin, Edward Sandford, -- 1856-1939 -- Correspondence; Mencken, H. L. -- 1880-1956 -- Correspondence; Paine, Albert Bigelow, -- 1861-1937 -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Pitz, Henry C. -- 1895-1976 -- Correspondence; Post, Augustus, -- 1873-1952 -- Correspondence; Pratt, George D. -- 1869-1935 -- Correspondence; Presbrey, Frank, -- 1855-1936 -- Correspondence; Remington, Frederic, -- 1861-1909 -- Correspondence; Rockwell, Norman, -- 1894-1978 -- Correspondence; Roosevelt, Edith Kermit Carow, -- 1861-1948 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Roosevelt, Theodore, -- 1887-1944 -- Correspondence; Seton, Ernest Thompson, -- 1860-1946 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Steele, Frederic Dorr, -- 1873-1944 -- Correspondence; Stone, A. J. -- 1859- -- Correspondence; Taft, Lorado, -- 1860-1936 -- Correspondence; Van Loon, Hendrik Willem, -- 1882-1944 -- Correspondence; Vreeland, Frederick K. -- 1874- -- Correspondence; Ward, John Quincy Adams, -- 1830-1910 -- Correspondence; West, James E. -- 1876-1948 -- Correspondence; Wister, Owen, -- 1860-1938 -- Correspondence; Woolf, S. J. -- 1880-1948 -- Correspondence; Wyeth, N. C. -- 1882-1945 -- Correspondence; Beard family; Beard family -- Correspondence; Roosevelt family -- Correspondence; Boy Scouts of America; Charles Scribner's Sons -- Correspondence; Culver Military Academy; Dan Beard Outdoor School for Boys (Pike County, Pa.); J.B. Lippincott Company -- Correspondence; Sons of Daniel Boone; Boys' life; Boys' life -- Correspondence; Boy Scouts -- Periodicals; Boy Scouts -- United States; Boys -- United States -- Societies and clubs; Camps -- Pennsylvania -- Pike County; Military education -- United States; Private schools -- Indiana -- Culver; Youth -- United States -- Societies, etc; Artists; Authors; Boy Scout leaders